PELATIHAN PUBLIC SPEAKING, MASTER OF CEREMONY (MC) DAN ICEBREAKING DALAM RANGKA MENINGKATKAN KEPERCAYAAN DIRI SISWA SISWI SMK SAID NAUM JAKARTA PUSAT - Redjeki Agoestyowati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Being able to speak in public, become an MC, and do icebreaking activities are skills that are needed now. These three activities are often used in various events, both formal and informal events, such as seminars, art performance, training, birthdays, inauguration, company gatherings and others. In those activities, people who can speak in public are definitely needed to give speeches, become MCs or do icebreaking, but many people feel less confident about speaking in public due to nervousness, or lack of practice, not used to it, or other reasons. Basically, the ability to speak in public can be learned and trained, the more often we do it, the more skilful and courageous will appear confidently. One form of public speaking activity is the Master of Ceremony (MC), which is an activity to guide an event, including several kinds of Programmes of formal, semi-formal, entertainment, birthday events, talk shows and so on. The opportunity to become an MC or the MC profession is currently very large and can be done by anyone, including students who are still in SMK. Therefore, it is necessary to provide training for students at Said Naum Vocational High School, Central Jakarta with the theme: Public Speaking, Master of Ceremony (MC) and Icebreaking Training in order to increase the self-confidence of Said Naum Vocational School students, Central Jakarta.